Autovadīšanai paredzēto briļļu lēcu ietekme uz redzes asumu un kontrastjutību - Hammar, Michelle Elisabeth Natalie (Latvijas Universitāte, 2023)
Maģistra darbs ir uzrakstīts angļu valodā uz 37 lapaspusēm. Tas satur 27 attēlus, 1 tabulaa, 2 pielikumu un 43 atsauces uz literatūras avotiem. Darba mērķis ir izvērtēt autovadītājiem paredzēto lēcu ietekmi uz redzes kvalitāti. Mērījumi tika veikti četros apgaismojuma apstākļos bez lēcas, ar autovadītājiem paredzēto lēcu un lēcu ar pretatspīdumu klājumu. Tika veikta aptauja par žilbšanas biežumu autovadītājiem un viņu informētību par autovadītājiem paredzētajām lēcām. Rezultāti parādīja, ka apgaismojuma apstākļi būtiski ietekmēja kontrastjutību. Lēcu veids neietekmēja redzes asumu un kontrastjutību.

This thesis is a 37-page document written in English that includes 27 figures, 1 table, 2 appendixes and 43 references. Its objective was to examine the impact of driver lenses on vision quality. Measurements were conducted in four lighting conditions: with no lens in front of the eye, with driving lenses, and with lenses that had an antireflective layer. A questionnaire was used to analyze the subjective feeling of glare disturbance while driving and the participants knowledge of driver lenses. The study found that the light conditions had a significant impact on the contrast sensitivity, but the lenses did not affect the visual acuity or contrast sensitivity. Additionally, glare was found to be most disturbing at night, and most participants were unfamiliar with driver lenses.
The Impact of Driving Spectacle Lenses on Visual Acuity and Contrast Sensitivity
Keywords: Klīniskā optometrija [Angļu val.]; Driver lenses; contrast sensitivity; visual acuity; glare